Peningkatan Produksi dan Pemasaran Jamur Tiram Putih dengan Memanfaatkan Baglog Tongkol Jagung di Usaha Kecil Menengah Oemah Jamur Tangerang: Enhancing Production and Marketing of White Oyster Mushrooms through the Utilization of Corn Cob–Based Baglogs in the Small and Medium Enterprise "Oemah Jamur", Tangerang - Wahyu Irawati; Adolf Jan Nexson Parhusip; Reisky Megawati Tammu; Nicolas Tunggul Adhigandewa; Amelia Ranindah Sagala; Alya Leonita Lamonta (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
The demand for white oyster mushrooms continues to increase due to their high nutritional content and relatively affordable price, making them a popular alternative source of plant-based protein. However, production of white oyster mushrooms in Tangerang has declined due to the limited availability of wood-based baglog raw materials, which are increasingly difficult to obtain. This Community Service (PkM) activity is a response to this problem by using corn cobs as an alternative baglog raw material at the Tangerang Oemah Jamur SME. The main objectives of the activity include increasing oyster mushroom productivity through the formulation of corn cob waste-based baglog, strengthening the marketing management of fresh products, and developing the marketing of processed products. The implementation methods included socialization, training, technology application, mentoring, evaluation, and sustainability planning. Three variations of baglog formulations were tested, namely: (1) corn cobs, (2) corn cobs + bran, (3) corn cobs + bran + molasses + ecoenzymes. The results showed that the combination of corn cobs with bran, molasses, and ecoenzymes produced faster mycelium growth than the other formulations. The post-harvest products developed included crispy mushrooms and mushroom nuggets, while the marketing strategy was implemented through vacuum packaging, e-commerce platforms, and minimarkets. This activity serves as the basis for optimizing the sustainable production and marketing of white oyster mushrooms.